Fabrication of porous materials for cooling and gas storage applications - Koh, Wei Jin (2018)
Metal organic frameworks (MOFs) are materials with three-dimensional porous microstructure formed by a network of metal nodes and organic linkers. There are many studies conducted to understand the adsorption properties of MOFs and its applications in gas storage, drug delivery and cooling systems. MOFs are being studied intensely is due to its flexible permutation and combination of metal nodes and organic linkers to create different three-dimensional porous structure with different useful properties such as low densities, large internal surface areas, and a regular network of pore sites. This report presents three types of MOFs, namely: aluminum fumarate, aluminum fumarate-NH2, and MIL-101-NH2. The experimental methods to synthesize these MOFs were investigated. The porous characteristics of MOFs were measured by Scanning Electron Microscopy (SEM), Powder X-ray Diffraction (XRD), Thermogravimetric Analysis (TGA), Nitrogen Adsorption methods. Water adsorption on these materials was subsequently investigated. This report also investigated the effects on adsorption properties with a modified MOFs structure by adding a NH2 organic linker. The three materials were successfully synthesized and it was found that aluminum fumarate exhibited superior adsorption properties with high water uptakes of 0.47g/g, BET surface area of 792.26m2/g, and pore volume of 0.926cm3/g. Water uptakes, BET surface area and pore volume of aluminum fumarate-NH2 was 0.22g/g, 325.54m2/g, 0.408cm3/g; while those of MIL-101-NH2 were 0.36g/g, 514.21m2/g, 0.283cm3/g.